Some generalizations of Kannan's theorems via σc-function and its application - Suprokash Hazra (Mathematical Modelling and Analysis, 2019)
In this article, we go on to discuss various proper extensions of Kannan’s two diﬀerent ﬁxed point theorems, and introduce the new concept of , which is independent of the three notions of simulation function, manageable functions, and R-functions. These results are analogous to some well-known theorems, and extend several known results in this literature. An application of the new results to the integral equation is also provided.